Hydrogel‐Based Flexible Electronics. Issue 14 (22nd February 2023) - Hu, Lixuan; Chee, Pei Lin; Sugiarto, Sigit; Yu, Yong; Shi, Chuanqian; Yan, Ren; Yao, Zhuoqi; Shi, Xuewen; Zhi, Jiacai; Kai, Dan; Yu, Hai‐Dong; Huang, Wei
Abstract: Flexible electronics is an emerging field of research involving multiple disciplines, which include but not limited to physics, chemistry, materials science, electronic engineering, and biology. However, the broad applications of flexible electronics are still restricted due to several limitations, including high Young's modulus, poor biocompatibility, and poor responsiveness. Innovative materials aiming for overcoming these drawbacks and boost its practical application is highly desirable. Hydrogel is a class of 3D crosslinked hydrated polymer networks, and its exceptional material properties render it as a promising candidate for the next generation of flexible electronics. Here, the latest methods of synthesizing advanced functional hydrogels and the state‐of‐art applications of hydrogel‐based flexible electronics in various fields are reviewed. More importantly, the correlation between properties of the hydrogel and device performance is discussed here, to have better understanding of the development of flexible electronics by using environmentally responsive hydrogels. Last, perspectives on the current challenges and future directions in the development of hydrogel‐based multifunctional flexible electronics are provided. Abstract : The latest methods of synthesizing advanced functional hydrogels and the state‐of‐art applications of hydrogel‐based flexible electronics in various fields are reviewed. More importantly, the correlation between properties of the hydrogel and device performance, to have better understanding of the development of flexible electronics by using environmentally responsive hydrogels are discussed. Last, perspectives on the current challenges and future directions in the development of hydrogel‐based multifunctional flexible electronics are provided.